Problems of Interpreting Maithili Complex Predicates in English (Research Journal on Multi-disciplinary Issues, 2021)
Every language has its own uniqueness and lets  its  users  develop  any other language in the way their first/mother one has been structured and conceptualized. The present paper attempts to make the English teachers teaching English in Maithili ecology be aware of expressing multi word concepts (complex predicates) of Maithili in English, which has been a common problem for school and campus level students as well. Both types of data sources (primary and secondary) were used, viz. the secondary for identifying the complex predicates and the primary for finding out the difficulties faced by the learners for expressing the Maithili CP concepts in English. The result shows that Maithili is very rich by its complex predicates with different types and all levels (school and campus) students having Maithili as their mother language are found to be expressing the CPs in the same way even in English which happens to be pragmatically unacceptable. The concept of Maithili CPs cannot be expressed in the multi word way but in a single word way. Finally some pedagogical implications are also suggested for handling such problems and carrying out the further researches in the respective field.